Mechanisms of formation of targeted complex insertions under the synthesis of a DNA molecule containing cis-syn cyclobutane thymine dimers - Grebneva, H.A. (Reports of the National Academy of Sciences of Ukraine, 2015)
The mechanism of formation of complex mutations has not been yet explained. Mutations are called complex if a DNA site with certain length and certain nucleotide composition is replaced by that with different length and different nucleotide composition. The author has proposed and developed a polymerase-tautomeric model of ultraviolet mutagenesis. The mechanism of formation of targeted complex insertions that are caused by cis-syn cyclobutane thymine dimers is proposed. The error-prone or SOS-synthesis of double-stranded DNA containing cis-syn cyclobutane thymine dimers TT*1, TT*2, and TT*5 in one of its strands is considered. Cis-syn cyclobutane thymine dimers TT*2 lead to frameshift mutations, i. e., to the insertions of one or more nucleotides. Cis-syn cyclobutane thymine dimers TT*1 and TT*5 cause the formation of substitution mutations. Thus, due to the formation of a DNA insertion, its portion is extended, and its nucleotide composition varies due to the formation of several base substitution mutations. As a result, a DNA portion with certain length and nucleotide composition is replaced by that with different length and different nucleotide composition. A targeted complex mutation appears.